2010
DOI: 10.1007/s10798-010-9125-5
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ views about technical education: implications for reforms towards a broad based technology curriculum in Malawi

Abstract: Internationally there has been concern about the direction of technical education and how it is positioned in schools. This has also been the case in Malawi where the curriculum has had a strong focus on skills development. However, lately there has been a call for enhancing technological literacy of students, yet little support has been provided for teachers to achieve this goal. This paper reports from a wider study that looked at teachers' existing views and practices in technical education in Malawi. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In addition to our findings on teachers' need for support, our participants mentioned several barriers to the integration of technology. Consistent with the existing literature on STEM integration (Chikasanda et al, 2011;Margot & Kettler, 2019;Park et al, 2017;Yu et al, 2021), most teachers referred to a lack of resources-namely, materials and school equipment (16 participants), lack of content knowledge (nine participants), time constraints (eight participants), and students' heterogeneity (seven participants). Our participants also referred to students' safety while working with tools and electricity (eight participants), the size of the classroom (five participants), the broad curriculum (four participants), and their self-inhibitions regarding technology (four participants).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to our findings on teachers' need for support, our participants mentioned several barriers to the integration of technology. Consistent with the existing literature on STEM integration (Chikasanda et al, 2011;Margot & Kettler, 2019;Park et al, 2017;Yu et al, 2021), most teachers referred to a lack of resources-namely, materials and school equipment (16 participants), lack of content knowledge (nine participants), time constraints (eight participants), and students' heterogeneity (seven participants). Our participants also referred to students' safety while working with tools and electricity (eight participants), the size of the classroom (five participants), the broad curriculum (four participants), and their self-inhibitions regarding technology (four participants).…”
Section: Discussionsupporting
confidence: 67%
“…Curricular and structural challenges refer to the inflexibility of students' schedules and curricular plans, along with the lack of financial support and technology resources in schools (Margot & Kettler, 2019). Several studies have reported that the broad and undefined curriculum standards are often perceived by teachers as some of the main challenges in integrating technology subjects in their classrooms (Chikasanda et al, 2011;Yu et al, 2021).…”
Section: Teachers' Perceptions Of the Integration Of Technology Educa...mentioning
confidence: 99%
“…Most of the published studies in Phase II discuss the stimulation of technology into the curriculum in the vocational education sector (Chikasanda et al. , 2011; Akuner et al.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published studies in Phase II discuss the stimulation of technology into the curriculum in the vocational education sector (Chikasanda et al, 2011;Akuner et al, 2012). Akuner et al (2012) state that technology practice in the curriculum will support teaching strategies that can be advantageous to the students.…”
Section: 4mentioning
confidence: 99%
“…There also has been no change in the applied engineering college-level educator requirements to deliver remedial, introductory, intermediate, and advanced technical content to students in traditional-classroom, hybrid/blended, and 100% online delivery settings. As reported in the 2013 report, many faculty members are not only teaching typical lecture courses but also being tasked with managing student laboratories, advising students, participating in professional association events, continued service in faculty governance committees, financial responsibilities, and continued personal professional development at high competency levels (Chikasanda, Otrel-Cass, & Jones, 2010). Many faculty members have forsaken education as a profession due to these factors.…”
mentioning
confidence: 99%